Magnetism and Photomagnetism of Prussian Blue Analogue Nanoparticles Embedded in Porous Metal Oxide Ordered Nanostructures. Issue 3 (24th October 2017) - Fornasieri, Giulia; Bordage, Amélie; Bleuzen, Anne
Abstract : Prussian blue analogues (PBAs) are key compounds in the field of molecular magnetism and photomagnetism. In parallel to the strong development of this class of compounds, many efforts have been devoted to produce PBAs in various shapes and sizes. In this microreview we focus on works reporting the use of porous metal oxide nanostructures as hard templates for controlling the size, shape and solid‐state organization of magnetic and photomagnetic PBA nanoparticles. The oxide matrices that have so far been developed and their characteristics are presented first. Then, the approaches that have been successfully used to control PBA formation within the pores of the matrices are described, as well as the morphology and environment of the functional nanoparticles. Lastly, the magnetic and photomagnetic properties of the nanocomposites are reviewed. Abstract : Beyond the design and study of molecular compounds with remarkable magnetic properties, many efforts have recently been made to control the shape and organization of molecular objects in solid matrices or on solid surfaces. We review the use of ordered nanostructured oxides as hard templates to control the size and organization of magnetic and photomagnetic Prussian blue analogue nanoparticles.